24. KNOWLEDGE AND PRACTICE ON ENVIRONMENTAL SANITATION OF HEALTH STAFFS AT THE NATIONAL EYES HOSPITAL, IN 2021 (Vietnam Journal of Community Medicine, 2023)
Background: The environment of hospital can be one of the sources of hospital infections. Goodenvironmental hygiene practices in hospitals help ensure the safety of patients and medical staff inmedical examination and treatment activities.Objectives: Describe the knowledge and practice of environmental sanitation of medical staff at theNational Eye Hospital and analyze some related factors.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 323 health workers (NVYT), National Eye Hospitalthrough questionnaires and observation using checklists. The research results show that theknowledge and practice of environmental sanitation in the control of hospital-acquired infections ofhealth workers is quite good.Conclusion: The rate of health workers with knowledge of environmental sanitation reached 70,6%.The rate of health workers with practices of environmental sanitation reached over 75%. There are4 factors related to knowledge including: age, working position, working time and professionalqualifications. Three factors related to practices including: Gender, working position and time oftraining on infection control (p
Keywords: Environmental sanitation, related factors, health workers.